Pengaruh Motivasi Kerja, Gaya Kepemimpinan, dan Budaya Organisasi Terhadap Kepuasan Kerja Karyawan (Studi pada PT. Bank Rakyat Indonesia (Persero),Tbk Kantor Wilayah Semarang) - Diantari Indah Widiatmayanti; Saryadi Saryadi; Sendhang Nurseto (Universitas Diponegoro, 2015)
AbstractThis study aims to determinate themselves the extend of the influence of work motivation, leadership style, and organizational culture to employee job satisfaction in Regional Office of PT Bank Rakyat Indonesia (Persero),Tbk Semarang. This type of research is explanotary research, that explain realationship between research variables. With a sample of this study were 57 respondents as appointed in the Slovin formula. This study uses quantitative analysis techniques using validity, rebilitas, simple linear regression, multiple linear regression.Result of calculation of the coefficient of determinations is 0,347. This suggest that the work motivation, leadership style, and organizational culture able to explain the variables performance of 34,70 percent. While 65,30 percent is influence with another variables that are not observed. Based on the result of the data analysis it can be conclude that influence of work motivation, leadership style, and organizational culture to job satisfaction employee of regional office of PT Bank Rakyat Indonesia (Persero),Tbk Semarang has a low level of closeness. This means that the higher work motivation, leadership style, and organizational culture will resulted the higher job satisfaction.